Two devices to facilitate the perception of pelvic floor muscle contraction in the sitting position in women with urinary incontinence: comparative analysis - Thais Naomi Sawada; Adriana Claudia Lunardi; Daniela Fantin Carro; Débora Françoes Porto; Leda Tomiko Yamada da Silveira; Elizabeth Alves Gonçalves Ferreira (Universidade de São Paulo, 2022)
ABSTRACT The use of support devices may facilitate the perception of pelvic floor muscle (PFM) contraction, which is difficult to be performed. Therefore, this study aimed to compare the perception of PFM contraction in the sitting position during the use of two different support devices on women with PFM dysfunction. This is a cross-sectional study performed with 37 women with stress or mixed urinary incontinence (UI). All women performed three free PFM contractions sitting on a chair, followed by three contractions using each support device (sand pads and a cylindrical foam, which provide sciatic and perineal support, respectively). Women scored the perception of PFM contraction from 1 to 5, as well as the perception of facilitation of contraction (higher grades show better results) and discomfort (higher grades show more discomfort) when compared with free contraction. The cylindrical foam presented similar results to sand pads for the perception of PFM contraction (2.84±1.61 vs. 3.19±1.43; p=0.34) and facilitation of contraction (3.38±1.34 vs. 3.19±1.54; p=0.61), as well as for their discomfort (1.83±1.23 vs. 1.5±1.16; p=0.20). Of all women, 57% preferred sand pads. Thus, both sand pads (sciatic support) and the cylindrical foam (perineal support) improved the perception of PFM contraction and facilitation of contraction in the sitting position of women with PFM dysfunction when compared with sitting with no device. The two devices presented no difference between them.